PENGARUH KEPEMIMPINAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PEMASARAN PT. NYONYA MENEER SEMARANG - Febrina Prihandini; Wahyu Hidayat; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2013)
The purpose of this study was to determine the effect of leadership variables , variable compensation and working environment variable to variable performance of employees of Marketing PT . Nyonya Meneer Semarang . This type of research is explanatory . In this study population there were 40 employees of the marketing department of PT . Nyonya Meneer Semarang and all were sampled by sampling saturated . Data were collected through questionnaires . Measurement scale using a Likert scale . Data analysis method used is correlation , simple and multiple linear regression with SPSS 16.0.The study concluded that : ( a) leadership in PT . Nyonya Meneer Semarang is good , so is the compensation available in PT . Nyonya Meneer Semarang is good and working environment in the PT . Nyonya Meneer Semarang is good ; ( b ) the effect of leadership on employee performance is strong at 0.639 , (c ) the effect of compensation on employee performance is stronger by 0.657 ; ( d ) the influence of the work environment on employee performance is quite strong at 0.473 , ( d ) simultaneously results demonstrate leadership , compensation and work environment has a strong influence on the performance of employees is 0.704 . Leadership and compensation variables have a greater influence than the work environment variables .